A Flavonoid-rich Zuccagnia punctata Extract Prevents High Fat Diet-induced Normal Weight Obesity in a Rabbit Model - Valoy, Agostina; Alarcón, Gabriela; Roco, Julieta; Zampini, Catiana; Isla, María Ines; Jerez, Susana (Planta Medica, 2022)
Oral administration of rich in flavonoids hydroalcoholic extract from Zuccagnia punctata (ZpE) improves lipid profile and prevents vascular dysfunction in hypercholesterolemic rabbits. This study aimed to evaluate the ability of ZpE to prevent metabolic and vascular alterations induced by high fat diet (HFD) on a metabolically obese and normal weight rabbit model. The major components of ZpE were analyzed by HPLC method. Rabbits were separated into six groups: 1-fed on standard chow (CD); 2-fed on HFD; 3, 4, 5- fed on HFD and orally administrated 2.5 mg, 5 mg or 10 mg GAE/day of ZpE, respectively (ZpE- HFD); 6- fed on HFD and orally administered 30 mg orlistat/day (Or-HFD). All diets were administrated by 6 weeks. The major compounds of ZpE identified were chalcones: 2′,4′-dihydroxy-3′-methoxychalcone and 2′,4′-dihydroxychalcone. Oral treatment with ZpE 5 mg GAE/day as well as orlistat prevented the HFD-induced increase of triglycerides, fasting glucose, intraperitoneal glucose test, white cells, and TyG index. Acetylcholine relaxation was reduced in arteries from HFD group and oral administration of ZpE reached this response to CD values. Contractile response to angiotensin II was lower in arteries from rabbits fed on HFD treated with ZpE 5 and 10 mg GAE/day than those of untreated rabbits. Moreover, ZpE could inhibit the activity of pancreatic lipase in vitro and in vivo. In conclusion the ZpE may prevent normal weight obesity by inhibiting the pancreatic lipase. Thus, the use of ZpE as a natural product in the prevention of metabolic syndrome and endothelial dysfunction is very promising.
Keywords: high fat diet; Zuccagnia punctata; Fabaceae; metabolic syndrome; flavonoids; endothelial function